Defaults and effortful tasks - Lars Behlen; Oliver Himmler; Robert Jäckle (Experimental Economics, 2023)
Nothing is known about the effectiveness of defaults when moving the target outcomes requires substantial effort. We conduct two field experiments to investigate how defaults fare in such situations: we change the university exam sign-up procedure in two study programs to "opt-out" (a) for a single exam, and (b) for many exams. Both interventions increase task uptake (exam sign-up). Concerning the outcomes which require effort, we find no effects for many exams. For a single exam, the opt-out increases task completion (exam participation) in the study program where the default arguably entails stronger endorsement. Within this program, the effects on successful task completion (exam passing) are heterogeneous: treated students who in the past were willing to communicate with the university (responsive individuals) invest more effort into exam preparation and are more likely to pass the exam than their control counterparts.For non-responsive individuals, we find increased sign-ups but no effects on the target outcomes. Defaults can thus be effective and may be an attractive policy option even when the target outcome requires substantial effort provision. It is, however crucial that the interventions target the appropriate individuals.
Keywords: C93; D02; D91; I23; J18; J24; 330; Default; Randomized field experiment; Higher education